Etnolinguistik komuniti Melayu Saribas, Sarawak (Jurnal Bahasa, 2008)
This is a descriptive study which will focus on the segmental phonology aspect of the Sarawak Malay-Saribas dialect, particularly the district of Debak, Saribas, Sarawak. The vocal and consonant phonemes found in the native speakers' speech of dialect were analyzed. The analysis was based on the theory of structural phonology. At the same time, some aspects of the Malay community in the district were also looked into. Findings reveal that the dialect has 27 phonemes; namely 19 consonants, 8 vocal and 1 diphthong. It is a dialect with its own linguistic features and is least influenced by other dialect like Kuching Malay dialect. It was deemed important to share and make this ethnolinguistic aspect of the Malay-Saribas community known because of the constant changes and the dynamics of the language.